Gender- and Age-Specific Differences in the Association of Hyperuricemia and Hypertension: A Cross-Sectional Study. (28th February 2019) - Lin, Xiaoyun; Wang, Xiqian; Li, Xin; Song, Lili; Meng, Zhaowei; Yang, Qing; Zhang, Wenjuan; Gao, Yuxia; Yang, Zhenwen; Cai, Heng; Bian, Bo; Li, Yongle; et al.
Abstract : Objective . Both hyperuricemia and hypertension have important clinical implications, but their relationship in terms of gender and age is still a matter of debate. In this study, we aimed to explore gender- and age-specific differences in this association between hyperuricemia and hypertension in a Chinese population. Methods . A total of 78596 ostensibly healthy subjects (47781 men and 30815 women) were recruited. The association between hyperuricemia and hypertension was analyzed by multivariate logistic regression, and the analyses were stratified by gender and age. Results . Overall prevalence of hypertension and hyperuricemia was significantly higher in males than in females. Increasing trends of hypertension prevalence in both genders as well as hyperuricemia prevalence in females were found along with aging. However, males showed a reduced trend in hyperuricemia prevalence with aging. Higher hypertension and hyperuricemia prevalence was found in young and middle-aged men than in women, but not in elderly people older than 70 years. Significantly increased risk of hypertension from hyperuricemia was found only in men with an adjusted odds ratio of 1.131 (P < 0.01 ), especially in the middle-aged male participants. However, such significant results were not found in women. Similarly, hyperuricemia was also an independent risk factor of increased systolic blood pressure and diastolic blood pressure in males, but not in females. Conclusion . We observed significantly higher overall prevalence of hyperuricemia and hypertension in men than in women. Men with hyperuricemia (particularly in middle age) had a significantly increased susceptibility of hypertension, while this significant association was not observed in women.